Seagrass Ecosystem Assesment for Dugong Conservation: Integrating Anthropogenic Activites and Oceanographic Parameters in East Java’s Coastal Waters - Dewi, Citra Satrya Utama; Ciptadi, Gatot; Wahyudi, Slamet; Wiadnya , Dewa Gede Raka; Semedi, Bambang; Sukandar, Sukandar; Isdianto, Andik; Sunuddin, Adriani; Herandarudewi, Sekar Mira; Tarno, Hagus (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research 1. The study successfully identified the utilization of coastal and marine areas within the research site. 2. Oceanographic parameters across the study area have been analyzed, providing insights into variations in environmental conditions favoring seagrass ecosystem resilience. 3. The structure of seagrass vegetation has been thoroughly observed, revealing differences in species composition, density, and coverage. 4. Furthermore, the study establishes the connectivity between coastal and marine spatial utilization, oceanographic factors, and seagrass ecosystem dynamics, highlighting their interdependent relationships.     Abstract This study aims to assess the ecological status of seagrass meadows and their relationship with dugong (Dugong dugon) habitats across four distinct ecological regions in East Java, Indonesia. Field assessments were conducted to evaluate seagrass community structure, oceanographic parameters, and the intensity of human activities. Seagrass distribution was mapped using Sentinel-2A satellite imagery, while seagrass health was evaluated through the Seagrass Ecological Quality Index (SEQI) and Importance Value Index (IVI). Statistical analyses, including Analysis of Variance (ANOVA) and Principal Component Analysis (PCA), were employed to identify significant differences and key environmental drivers. The results revealed marked spatial variation in oceanographic characteristics and seagrass coverage (p < 0.05). PCA showed that anthropogenic factors—particularly marine space utilization such as aquaculture and coastal development—were major contributors to seagrass degradation. Elevated nutrient concentrations were also associated with declining seagrass health, indicating land-based pollution as a dominant stressor. These findings underline the urgent need for integrated coastal zone management. Strengthening conservation policies, reducing terrestrial runoff, and implementing sustainable marine spatial planning are critical to safeguard seagrass ecosystems and ensure the long-term survival of dugong populations in Indonesian waters.